In debt to the time-bank: the manipulation of working time in Indian garment factories and 'working dead horse'. (February 2017) - Jenkins, Jean; Blyton, Paul
In this article we focus on the creation of debt relations between workers and their workplace as a tool of managerial control in the garment factories of Bangalore, India. The currency of indebtedness in this case is working time and our focus is the manipulation of hours of work at the base of the international, buyer-driven, garment supply chain. In illuminating debt relations and worker dependency as an element of managers' repertoire of control, we compare a system known as 'comp-off' in contemporary Indian factories with the historical precedent of a system known as 'working dead horse' in Britain. Our comparison illuminates how value is extracted from workers and how old control systems are updated within the labour process, in a feminized sector where workers' associational power is weak and social downgrading is one means by which employers can offload risk, maximize flexibility and secure their position at the local level.